Pendampingan Manajemen Keuangan Umkm untuk Meningkatkan Kinerja Usaha Mikro di Desa Asinan Ambarawa Semarang - Hani Krisnawati; Rita Andini; Y. Sutomo; Sukirman Sukirman; Nur khotib Nidayatullah (Lembaga Pengembangan Kinerja Dosen, 2026)
This community service program aims to improve the performance of micro-enterprises through MSME financial management assistance in Asinan Village, Ambarawa. The main problems faced by micro-business actors include low financial literacy, the absence of systematic financial records, and the mixing of personal and business finances. The method used was a participatory approach through stages of training, mentoring, direct practice (learning by doing), and evaluation. This activity involved 25 micro-business actors as participants. The results showed a significant improvement in financial literacy and financial management practices. As many as 75% of participants were able to carry out simple financial recording, 70% began separating personal and business finances, and 65% were able to prepare simple profit and loss reports. In addition, there was an improvement in business performance indicated by an increase in turnover of 20–25% and an increase in the number of customers. Continuous mentoring proved to be more effective than conventional training in improving business performance. Therefore, the financial management assistance model can serve as an effective strategy for empowering MSMEs and improving the community’s economy.